Penggunaan MKJI 1997 dalam Rekomendasi Kebijakan Pengaturan Sinyal Lalu Lintas di Pekanbaru: Studi Kasus : Simpang Parit Indah - Muttaqin, Muchammad Zaenal; Zalfa Zutia, Attila (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2025)
The signaled intersection of Jalan Parit Indah in Pekanbaru City is one of the significant congestion points due to the high volume of vehicles and the suboptimal timing of signals. This study aims to evaluate the performance of intersections based on the Indonesian Road Capacity Manual 1997 (MKJI) method and to prepare recommendations for more effective signal timing. The research was conducted for three days during the peak hours of morning, noon, and evening, with the collection of primary data in the form of vehicle volume, speed, and intersection geometry. The data were analyzed using the 1997 MKJI approach to calculate the saturation current, degree of saturation, queue length, and delay in existing conditions and conditions after alternative signal settings were applied. The results of the analysis showed that in the existing conditions, the intersection was within the LOS F service level, with high queue lengths and delays. After modifying the signal time based on the MKJI method, there was a decrease in the average queue length by 20 meters and an improvement in traffic delays. This study provides evidence that signal time optimization based on MKJI 1997 can be the basis for the formulation of technical policies for urban traffic regulation, especially at intersections with high traffic flow. The recommendations of the results of this study are expected to be input for the Pekanbaru City Transportation Agency in making decisions related to improving the efficiency of signaled intersections.